Protective Role of the ACE2/Ang-(1–9) Axis in Cardiovascular Remodeling - María Paz Ocaranza; Jorge E. Jalil (International Journal of Hypertension)
Despite reduction in cardiovascular (CV) events and end-organ damage with the current pharmacologic strategies, CV disease remains the primary cause of death in the world. Pharmacological therapies based on the renin angiotensin system (RAS) blockade are used extensively for the treatment of hypertension, heart failure, and CV remodeling but in spite of their success the prevalence of end-organ damage and residual risk remain still high. Novel approaches must be discovered for a more effective treatment of residual CV remodeling and risk. The ACE2/Ang-(1–9) axis is a new and important target to counterbalance the vasoconstrictive/proliferative RAS axis. Ang-(1–9) is hydrolyzed slower than Ang-(1–7) and is able to bind the Ang II type 2 receptor. We review here the current experimental evidence suggesting that activation of the ACE2/Ang-(1–9) axis protects the heart and vessels (and possibly the kidney) from adverse cardiovascular remodeling in hypertension as well as in heart failure.